Banwa the multidisciplinary journal of UP Mindanao.
A peer-reviewed academic journal published biannually by the University of the Philippines Mindanao under the auspices of the Office of Research, which addresses relevant issues in the fields of the humanities, natural and applied sciences, social sciences, and management and economics. The journal is devoted to promoting scholarship and insightful debate by publishing a broad range of critical and scholarly articles, research reports, reviews, short notes, lectures, policy statements, and advocacies across the various disciplines, written by both emerging and established scholars, local and international.